2014
DOI: 10.1080/00927872.2013.827692
|View full text |Cite
|
Sign up to set email alerts
|

Whittaker Categories and Whittaker Modules for Lie Superalgebras

Abstract: Following analogous constructions for Lie algebras, we define Whittaker modules and Whittaker categories for finite-dimensional simple Lie superalgebras. Results include a decomposition of Whittaker categories for a Lie superalgebra according to the action of an appropriate sub-superalgebra; and, for basic classical Lie superalgebras of type I, a description of the strongly typical simple Whittaker modules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…The sets Φ + 0 , Φ + 1 are given as follows: In this subsection, we will construct composition series of standard Whittaker modules of N (ζ) explicitly by finding their Whittaker vectors. Similar computation was also given in [BCW,Section 5.1], where the authors concluded that all standard Whittaker modules are simple. However, by [CM,Theorem 6.7] and [MS1,Proposition 2.1(3)] there exist reducible standard Whittaker modules; see Section 5.3.3 for more details.…”
Section: 32supporting
confidence: 67%
See 3 more Smart Citations
“…The sets Φ + 0 , Φ + 1 are given as follows: In this subsection, we will construct composition series of standard Whittaker modules of N (ζ) explicitly by finding their Whittaker vectors. Similar computation was also given in [BCW,Section 5.1], where the authors concluded that all standard Whittaker modules are simple. However, by [CM,Theorem 6.7] and [MS1,Proposition 2.1(3)] there exist reducible standard Whittaker modules; see Section 5.3.3 for more details.…”
Section: 32supporting
confidence: 67%
“…We should mention that the Part (1) in Theorem 8 generalizes the construction of simple modules in [BCW,Section 4], where the case of some basic classical Lie superalgebras of type I was considered.…”
Section: Simple and Standard Whittaker Modulesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are several differences and some features that are new in the super case. It has been observed in [5], Mathematics Subject Classification: 17B65; 17B68;17B70. 1 simple finite-dimensional modules for a finite-dimensional nilpotent Lie superalgebra are not always one-dimensional [25].…”
Section: Introductionmentioning
confidence: 99%